Investment-specific technology shocks and international business cycles: An empirical assessment - Federico S. Mandelman; Pau Rabanal; Juan F. Rubio-Ramírez; Diego Vilán (Federal Reserve Bank of Atlanta, 2010)
In this paper, we first introduce investment-specific technology (IST) shocks to an otherwise standard international real business cycle model and show that a thoughtful calibration of them along the lines of Raffo (2009) successfully addresses the quantity, international comovement, Backus-Smith, and price puzzles. Second, we use OECD data for the relative price of investment to build and estimate these IST processes across the United States and a rest of the world aggregate, showing that they are cointegrated and well represented by a vector error correction model (VECM). Finally, we demonstrate that when we fit such estimated IST processes in the model instead of the calibrated ones, the shocks are actually not as powerful to explain any of the four mentioned puzzles.
Keywords: E32; F32; F33; F41; 330; international business cycles; cointegration; investment-specific technology shocks